Rochester Rehabilitation Center : a nonprofit contemplates the purchase of a greeting card company - Oster, Sharon M.; Garstka, Stanley J.; Elias, Jaan ([London] : SAGE, 2016)
In 2001, George Gieselman, president of the Rochester Rehabilitation Center, was considering a unique proposition for his nonprofit organization. A Rochester-based greeting card company, Parrett Paper, had fallen on hard times and was looking for a buyer. The Center already operated a division, The Out-Source, which provided direct employment for the disabled individuals who were the clients of the Center. If The Out-Source purchased the card company, the business could potentially generate additional jobs for the disabled as well as provide a source of income. However, the greeting card business seemed to be unlike the other contract work provided by The Out-Source division and therefore might strain the managerial resources of the organization.
Originally Published in: Oster, S., Garstka, S., Elias, J. (2010). Rochester Rehabilitation Center: A nonprofit contemplates the purchase of a greeting card company. 10-034. New Haven, CT: Yale School of Management, Yale University.
Description based on online resource; title from home page (viewed on May 3, 2016).
Keywords: elektronické knihy; electronic books; Rochester Rehabilitation Center; Strategic alliances (Business) -- Case studies; Consolidation and merger of corporations -- Case studies; Nonprofit organizations -- Management -- Case studies